Jingui Shenqi Pills Regulate Bone-Fat Balance in Murine Ovariectomy-Induced Osteoporosis with Kidney Yang Deficiency. (7th September 2020) - Shang, Qi; Zhao, Wenhua; Shen, Gengyang; Yu, Xiang; Zhang, Zhida; Huang, Xuan; Qin, Weicheng; Chen, Guifeng; Yu, Fuyong; Tang, Kai; Chen, Honglin; Li, Juanmin; et al.
Abstract : Jingui Shenqi Pills (JGSQP) have been a staple of traditional Chinese medicine for thousands of years, used primarily as a treatment for kidney yang deficiency (KYD). In vitro analyses of JGSQP revealed strong induction of osteogenic differentiation and inhibition of adipogenic differentiation in bone-marrow-derived mesenchymal stem/stromal cells. However, the mechanisms by which JGSQP regulate the bone-fat balance in murine ovariectomy-induced osteoporosis with KYD have not been reported. Materials and Methods . Two-month-old female C57BL/6 mice were divided randomly into three groups: those receiving a sham operation (Sham); those undergoing bilateral ovariectomy and selection of KYD syndrome (Model); and those subjected to both bilateral ovariectomy and KYD syndrome selection for 8 weeks, followed by JGSQP treatment for 4 weeks (JGSQP). In the Sham and Model groups, mice were given the same dose of distilled water orally for 4 weeks. Animals from all three groups were euthanised at the 12th week. Vertebral microarchitecture and histomorphology were examined by micro-CT and H&E staining, respectively. In addition, we examined the mRNA expression of Akt, Wnt10b, Osterix (Osx), Fndc5, PPARγ, and Fabp4, as well as the protein of AKT, phosphorylation-AKT (p-AKT), BMP2, COL1A1, and FNDC5. Results . JGSQP treatment improved bone microarchitecture and mitigated histomorphological damage relative to the Model group. The osteoblast number (Ob.N/BS) and area (Ob.S/BS) were increased, whereas adipocyte number (adipocyte/tissue area) and area (adipocyte area/tissue area) were decreased in the JGSQP group. JGSQP treatment reduced the mRNA expression of Akt and adipogenesis-related genes ( Fndc5, PPARγ, and Fabp4 ) while promoting osteogenesis-related genes ( Wnt10b and Osx ) mRNA expression. Additionally, the expression of p-AKT, BMP2, and COL1A1 proteins was increased and FNDC5 protein expression was decreased after JGSQP treatment. Conclusions . JGSQP treatment reversed murine ovariectomy-induced osteoporosis with KYD by controlling bone-fat balance via AKT pathway.